Implementation of Scientific Literacy in The Independent Curriculum (Merdeka Curriculum) at Elementary School - Ratih Purnama Pertiwi; Arini Rosa Sinensis; Sri Enggar Kencana Dewi; Tri Ratna Dewi; Resti Septikasari (JIP Jurnal Ilmiah PGMI, 2023)
This research aims to describe and analyze the implementation of scientific literacy in the Independent Curriculum (Merdeka Curriculum) for elemenary school. The steps include planning learning with scientific literacy, checking implementation of the Independent Curriculum, and evaluating the learning process with scientific literacy. The method used is descriptive qualitative. The subjects of this research were Headmaster and teachers at 2 State elementary school of Gumawang, East Ogan Komering Ulu (OKU). Data collection through observation, interviews and document analysis related to the implementation of scientific literacy in the Merdeka curriculum. The validity of the collected data was tested using data and source triangulation techniques. The research results show that the implementation of scientific literacy in the Independent Curriculum in 2 State elementary school of Gumawang has experienced significant development. This is demonstrated by (1) A learning approach based on inquiry and experimentation, (2) Implementation of learning designed to emphasize in-depth understanding of scientific concepts and their application in everyday life, (3) The evaluation process carries out three evaluations, namely in cognitive, affective and psychomotor domains. The implementation of scientific literacy in the Meredeka Curriculum at 2 State elementary school of Gumawang is already underway in several driving schools, but there are several challenges that must be faced, including the lack of resources and training for teachers in adopting a more interactive scientific literacy approach, this is because there are still many teachers who are not used to it. with innovative learning methods that adopt the application of scientific literacy. Observation results show that reading literacy in elementary education level students is one aspect thathas not been fully implemented well. This is due to the lack of literacy among students. So the evaluation and measurement of scientific literacy skills needs to be improved to ensure the achievement of curriculum goals. This research provides an important contribution to understanding the implementation of scientific literacy in the Independent Curriculum at the elementary education level. The results of the research can be a basis for further development in efforts to improve the quality of education at the elementary level, with a focus on developing students' scientific literacy.